New Type of Thermal Moisture Sensor for in‐Textile Measurements. Issue 12 (14th February 2019) - Schönfisch, David; Göddel, Michael; Blinn, Jörg; Heyde, Christian; Schlarb, Heiko; Deferme, Wim; Picard, Antoni
Abstract : The measurement of moisture in textile materials worn on or near the skin can be performed for a variety of reasons, for example, to analyze the amount of perspiration in clothing, wound fluid in bandages or even urine in diapers or bed sheets. Conventional moisture measurement methods, such as electrical resistance or capacitance measurement, can be susceptible to cross sensitivities to electrical fields or ionic impurities, often occurring in measurements close to the human body. The very reliable gravimetric methods are too bulky and difficult to be integrated in portable and online measurements. In this paper, the authors present a "transient heat moisture sensor" (THMS) which is small and comparatively easy to integrate into textiles. The authors describe the measurement principle and present a sensor element manufactured with thin film technologies. The analytical description of the sensor fits to both, experimental data and the result of first numerical analysis (COMSOL Multiphysics). The authors demonstrate how to limit the sensors spatial sensitivity to a thin layer of textile without being influenced by the adjacent environment by proper timing of the signal readout. Abstract : Precise measurement of moisture in textile materials is of interest in many different topics. In this work, the authors present a novel method and a microtechnical sensor for the measurement of moisture in thin and porous layers. The authors fully describe and analyze the thermal based method and demonstrate its application with a textile typical for clothing.